The DFM Control System Based on PLL - Andrzej Popenda (Communications - Scientific letters of the University of Zilina, 2009)
A specific structure of control system with double fed machine (DFM) is studied in the paper. The DFM is assumed to be a generator with stator winding connected to the power grid and it produces active and reactive powers. A command vector controlling DFM is transformed to the rotor-oriented coordinate system using angle of transformation. The angle of transformation is estimated in the system by applying a phase locked loop (PLL).Moreover, an example of application of pulse phase locked loop for estimation of voltage vector components is presented in the paper. In conclusion the properties of proposed PLL-based control systems are compared with properties of systems known from radio engineering and telecommunications described in the first chapter of the paper.